Building The Competitive Advantages Of MSMEs Through Increasing The Capacity Of Business Model Innovation - Nugroho, Agung; Fontana, Avanti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Business model innovation is one of the main activities that needs to be carried out by companies to maintain competitiveness in today's digital economy. Although research on business models has increased since the 1990s, little is known about the practice of business model innovation in Small, Micro and Medium Enterprises (MSMEs) in Indonesia. This study addresses these research gaps and focuses on investigating the triggers and outcomes of business model innovation in SMEs. The partial least squares path modeling (PLS-PM) method is used to test the model empirically using data collected in 2021 from 75 MSMEs in Indonesia. The results show that the innovation level of SMEs has a positive impact on business model innovation. On the contrary, The business environment and information technology do not have a direct effect on the level of business model innovation. In addition, the results show that the Business Model Innovation Level has a positive impact on the Business Model Innovation Outcome and subsequently on the overall business performance. The results of this study contribute to knowledge in the field of MSME business model innovation and offer useful insights for MSMEs who intend to innovate their business models.